IMPACT OF FDI ON ECONOMY GROWTH: A COMPARISON OF SOUTH ASIAN STATES & CHINA - Taqadus Bashir; Ayesha Mansha; Rizwana Zulfiqar; Rabia Riaz (European Scientific Journal, ESJ, 2014)
This paper makes a comparison of the impact of Foreign Direct investment on the economies of South Asian states including Pakistan, India, Bangladesh and Sri Lanka with China. The paper attempts to investigate that what are the differences between the economies of South Asia region and China. For study purpose annual data are used. The variables selected are FDI, External Debt, and Remittances. Analytical tools of OLS test and granger causality test are used to analyze the data. The result confirmed the fast growing economic development of China as compared with states of South Asia. The results confirmed that China is much faster growing economy than South Asia region. In order to attract direct investment into the of South Asian states, there is a need to develop infrastructure, stabilized political environment, law and order situation, healthy economic environment, curtailing on external debt, tax exemption. If these countries give due attention to FDI role in economic development FDI can facilitate human capital formation, domestic investment and technology transfer in the region and they can also develop their economies much like that of China.